Causal effects of gut microbiota on the prognosis of ischemic stroke: evidence from a bidirectional two-sample Mendelian randomization study - Zhu, Anning; Li, Peng; Chu, Yuzhou; Wei, Xiuxiang; Zhao, Jiangna; Luo, Longfei; Zhang, Tao; Yan, Juntao (Frontiers in Microbiology, 2024)
Increasing research has implicated the possible effect of gut microbiota (GM) on the prognosis of ischemic stroke (IS). However, the precise causal relationship between GM and functional outcomes after IS remains unestablished.Data on 211 GM taxa from the MiBioGen consortium and data on prognosis of IS from the Genetics of Ischemic Stroke Functional Outcome (GISCOME) network were utilized as summary-level data of exposure and outcome. Four kinds of mendelian randomization (MR) methods were carried out to ascertain the causal effect of GM on functional outcomes following IS. A reverse MR analysis was performed on the positive taxa identified in forward MR analysis to determine the direction of causation. In addition, we conducted a comparative MR analysis without adjusting baseline National Institute of Health Stroke Scale (NIHSS) of post-stroke functional outcome to enhance confidence of results in main analysis.Four taxa were identified to be related to stroke prognosis in both main and comparative analysis. Specifically, genus Ruminococcaceae UCG005 and Eubacterium oxidoreducens group showed significantly negative effects on stroke prognosis, while genus Lachnospiraceae NK4A136 group and Lachnospiraceae UCG004 showed protective effects against stroke prognosis. Reverse MR analysis did 2 not support a causal role of stroke prognosis in GM. No evidence of heterogeneity, horizontal pleiotropy and outliers were found.This MR study provided evidence that genetically predicted GM had a causal link with post-stroke outcomes. Specific gut microbiota taxa associated with IS prognosis were identified, which may be helpful to clarify the pathogenesis of ischemic stroke and making treatment strategies.